2011
DOI: 10.1002/trtr.01036
|View full text |Cite
|
Sign up to set email alerts
|

Building Fluency Through the Phrased Text Lesson

Abstract: This Teaching Tip article explores the importance of phrasing while reading. It also presents an instructional intervention strategy for helping students develop greater proficiency in reading with phrases that reflect the meaning of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…'ye göre akıcılık genel olarak, sesli okurken birinin sesinde duyulabilen uygun ifadedir. Akıcılık, metindeki kelimeleri doğru ve hızlı okumanın yanında metnin anlamını yansıtan bir ifade ile okumaktır (Rasinski, Padak, McKeon, Wilfong, Friedauer, & Heim, 2005;Rasinski, Yıldırım, & Nageldinger, 2011). Akıcılık, metnin anlamını verecek biçimde nerede vurgu yapılacağını, nerede duraklanacağını bilmeyi gerektirir.…”
Section: Akıcı Okumaunclassified
“…'ye göre akıcılık genel olarak, sesli okurken birinin sesinde duyulabilen uygun ifadedir. Akıcılık, metindeki kelimeleri doğru ve hızlı okumanın yanında metnin anlamını yansıtan bir ifade ile okumaktır (Rasinski, Padak, McKeon, Wilfong, Friedauer, & Heim, 2005;Rasinski, Yıldırım, & Nageldinger, 2011). Akıcılık, metnin anlamını verecek biçimde nerede vurgu yapılacağını, nerede duraklanacağını bilmeyi gerektirir.…”
Section: Akıcı Okumaunclassified
“…We chose to read the story ourselves to help the children understand the text more easily. It seems that emerging readers can engage with a text with demanding vocabulary and facts and learn to read more fluently if the story is read sympathetically by a more advanced reader (Pennac, ; Rasinski, Yildirim, & Nageldinger, ). In addition, a teacher reading aloud to children will inspire those children to read more by themselves (Julkunen, ).…”
Section: Implementing Literature‐based Follow‐up Storiesmentioning
confidence: 99%
“…Many studies have demonstrated that children develop better literacy skills when read‐alouds are followed by integrated activities (Molloy, ; Rasinski et al., ). In our study, literacy was fostered by supporting children's engagement and imagination in diverse ways.…”
Section: Closing Thoughtsmentioning
confidence: 99%
“…The panel reviewed the scientific literature relevant to learning to read, having established explicit a priori criteria for what kinds of studies would be considered. Those criteria excluded studies that educators value: mainly, observational, quasi-ethnographic studies of individual schools, teachers, classrooms, and children that do not attempt to conform to basic principles of experimental design or data analysis (see, e.g., Barton & Hamilton, 1998; Rasinski et al, 2011). The report was therefore of little interest, to many educators except as evidence for a scientistic bias at odds with the educational establishment's core values (Krashen, 2001).…”
Section: What About How Reading Is Taught?mentioning
confidence: 99%